Intraperitoneal Injection Is Not a Suitable Administration Route for Single-Walled Carbon Nanotubes in Biomedical Applications - Xudong Liu; Qing Guo; Yuchao Zhang; Jinquan Li; Rui Li; Yang Wu; Ping Ma; Xu Yang (SAGE Publishing, 2016)
Given the extensive application of carbon nanotubes (CNTs) in biomedical fields, there is increasing concern regarding unintentional health impacts. Research into safe usage is therefore increasingly necessary. This study investigated the responses of the mouse brain to single-walled CNTs (SWCNTs) delivered via intraperitoneal (IP) injection and compared these results with the previous study where SWCNTs were delivered via intravenous (IV) injection so as to explore which administration route is potentially better for SWCNTs application. This study suggests SWCNTs delivered via IP injection can have negative effects on the mouse brain through oxidative stress and inflammation at high concentration exposure, but these responses were not consistent and showed no dose-dependent effect. In a previous study, the results showed that IV-delivered SWCNTs induced a more consistent and dose-dependent effect. The comparison of the 2 studies suggested that using SWCNTs at a safe dosage delivered via IV injection may be a better administration route for SWCNTs in biomedical applications.